INTEGRATING MULTICULTURAL ISLAMIC VALUES IN EARLY CHILDHOOD EDUCATION: A CASE STUDY FROM CENTRAL ACEH, INDONESIA - Muhammad Riza; Indra Indra (Jurnal As-Salam, 2026)
This article investigates the integration of multicultural Islamic educational values in early childhood learning, with a specific focus on TK Buah Hati Takengon, Central Aceh, Indonesia. Grounded in the local Gayo cultural context, this study examines how the school incorporates Islamic values and multicultural principles into its curriculum and pedagogical practices as a strategy to foster moderate Islamic education in a religious and ethnically diverse community. Employing a qualitative case study approach, data were collected through semi-structured interviews with eight participants (three teachers, two school administrators, and three parents), classroom observations conducted across ten sessions over two months (March–April 2025), and document analysis of curriculum materials and lesson plans. The findings reveal three interrelated strategies: (1) integration of multicultural Islamic values in the curriculum through culturally responsive materials; (2) promotion of diversity and tolerance through cultural celebrations, open classroom dialogue, and peer interaction activities; and (3) inclusive pedagogical strategies that accommodate diverse learning styles alongside active parental involvement. The scientific novelty of this study lies in its documentation of a localized model of early childhood Islamic education that harmonizes tawhid-based moral values with Gayo cultural practices, offering a replicable framework for multicultural Islamic pedagogy in pluralistic societies. This study contributes to educational policymakers, practitioners, and researchers working to design inclusive Islamic education curricula that respond to multicultural realities in Indonesia and beyond.